KINERJA GURU DALAM IMPLEMENTASI KURIKULUM 2013 DI SMA ISLAM AL-MA’ARIF PANDAN INDAH KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Bahman Bahman; Dian Hidayati (Academy of Education Journal, 2021)
Teacher performance is a necessity in improving the quality of learning services which includes the implementation of the curriculum for all components of the learning eye. The curriculum is a collection; the contents, objectives, and methods used by the teacher to achieve educational goals in school. This study aims to determine the teacher's performance and the obstacles faced by ISLAM AL-MA'ARIF high school teachers Pandan Indah district Lombok Tengah province Nusa Tenggara Barat in the implementation of the 2013 curriculum. To achieve this goal, this study uses a descriptive qualitative approach. While the subjects of the study were school supervisors, principals, deputy principals in the curriculum, K-13 assistant teachers and subject teachers. Data collection techniques are carried out through interviews, observation, and documentation studies. The data analysis procedure is data reduction, data display, and data verification.